Significant East Asian Affinity of the Sichuan Hui Genomic Structure Suggests the Predominance of the Cultural Diffusion Model in the Genetic Formation Process - Liu, Yan; Yang, Junbao; Li, Yingxiang; Tang, Renkuan; Yuan, Didi; Wang, Yicheng; Wang, Peixin; Deng, Shudan; Zeng, Simei; Li, Hongliang; Chen, Gang; Zou, Xing; et al. (Frontiers in Genetics, 2021)
The ancestral origin and genomic history of Chinese Hui people remain to be explored due to the paucity of genome-wide data. Some evidence argues that an eastward migration of Central Asians gave rise to modern Hui people, which is referred to as the demic diffusion hypothesis; other evidence favors the cultural diffusion hypothesis, which posits that East Asians adopted Muslim culture to form the modern culturally distinct populations. However, the extent to which the observed genetic structure of the Hui was mediated by the movement of people or the assimilation of Muslim culture also remains highly contentious. Analyses of over 700K SNPs in 109 western Chinese individuals (49 Sichuan Hui and 60 geographically close Nanchong Han) together with the available ancient and modern Eurasian sequences allowed us to fully explore the genomic makeup and origin of Hui and neighboring Han populations. The results from PCA, ADMIXTURE, and allele-sharing-based f-statistics revealed a strong genomic affinity between Sichuan Hui and Neolithic-to-modern Northern East Asians, which suggested a massive gene influx from East Asians into the Sichuan Hui people. Three-way admixture models in the qpWave/qpAdm analyses further revealed a small stream of gene influx from western Eurasians into the Sichuan Hui people, which was further directly confirmed via the admixture event from the temporally distinct Western sources to Sichuan Hui people in the qpGraph-based phylogenetic model, suggesting the key role of the cultural diffusion model in the genetic formation of the Sichuan Hui. ALDER-based admixture date estimation showed that this observed western Eurasian admixture signal was introduced into the Sichuan Hui during the historic periods, which was concordant with the extensive western-eastern communication along the Silk Road and historically documented Hui migration history. In summary, although significant cultural differentiation exists between Hui people and their neighbors, our genomic analysis showed their strong genetic affinity with modern and ancient Northern East Asians. Our results support the hypothesis that the Sichuan Hui arose from a mixture of minor western Eurasian ancestry and predominant East Asian ancestry.